2005
DOI: 10.1111/j.1464-410x.2005.05764.x
|View full text |Cite
|
Sign up to set email alerts
|

New life after prostate brachytherapy? Considering the fertile female partner of the brachytherapy patient

Abstract: RESULTSThree reported cases of pregnancy showed the men to have viable counts of within several or all of the parameters of the World Health Organisation criteria for normal semen analysis. CONCLUSIONSThese cases provide a cautionary tale and suggest that all men being treated with prostate brachytherapy should be counselled about the possibility of continued fertility. Documentation of this 'risk' on the consent form will allow for proper discussion of this issue in a clinical and medicolegal context. The key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Grocela et al . discussed the case of three spontaneous conceptions following prostate brachytherapy in men with organ confined disease (Grocela et al ., ). Similar to our patient, Steinsvik and colleagues also reported a case in which a 60‐year‐old man fathered a child four years after EBRT with concomitant ADT (Steinsvik et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Grocela et al . discussed the case of three spontaneous conceptions following prostate brachytherapy in men with organ confined disease (Grocela et al ., ). Similar to our patient, Steinsvik and colleagues also reported a case in which a 60‐year‐old man fathered a child four years after EBRT with concomitant ADT (Steinsvik et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…As older men generally are not considering future fertility, there has been little impetus for formally evaluating sterility after treatment for prostate cancer. Although a few case reports and case studies have identified a few men who have procreated following definitive radiation, these studies never reported whether formal paternity testing was performed to confirm fatherhood [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Based on studies in cancer survivors, high‐dose RT of the prostate has been assumed to affect fertility by arresting spermatogenesis and/or altered or discontinued production of the seminal fluid (low volume, changed composition) [6–8]. After implantation of 125 I‐seeds the reported doses to the testicles are 0.03–2.5 Gy [3,4]. The use of 125 I seeds implies low‐dose rate RT.…”
Section: Discussionmentioning
confidence: 99%
“…Scattered testicular irradiation during pelvic external beam radiotherapy (EBRT) and short‐term androgen ablation cause at least transient azoospermia, but there are no reports on sperm counts after EBRT in patients with prostate cancer. However, prostate brachytherapy is claimed to preserve spermatogenesis in some patients [3,4]. A reduction in the seminal fluid volume after RT might add to reduced fertility, due to arrest of spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%